Taxa de cesariana por meio da Classificação de Robson no estado do Pará durante os anos de 2019 a 2021 - SILVA, César Henrique da (2025)
Introduction: in recent decades, there has been a significant increase in cesarean deliveries across the globe, with Brazil having the second highest rate of cesarean sections in the world (BOERMA, 2018; DIAS, 2022). It should be noted that the World Health Organization (WHO) recommends that the ideal cesarean section rate should range from 10% to 15% in a country; values higher than these are not associated with a reduction in the maternal, perinatal and neonatal mortality rates, considering that some of the surgical risks that cesarean section offers to pregnant women correspond to pelvic floor dysfunction and a higher risk of infection; for the baby, asthma; for a pregnancy subsequent to perinatal death. In fact, there is a need for a tool that allows an in-depth study of the factors that permeate the high rate of deliveries via high birth today; the tool that the WHO recommends is the Robson classification, a means that groups obstetric characteristics to form ten groups that are mutually exclusive and entirely inclusive of each other (WHO, 2017). Objective: This study aims to use Robson's classification to study the factors that influence cesarean section rates in the State of Pará according to the ten groups of Robson's classification, with a view to proposing an improvement in the theoretical arsenal of scientific studies in relation to this theme in the State of Pará. Methodology: this is an analytical, descriptive and ecological cross-sectional observational epidemiological study, having as unit of analysis the municipalities, by mesoregions, of the State of Pará with a time interval between 2019 and 2021, in which the data were obtained from the Information System on Live Births of the Ministry of Health (Sinasc) through the Datasus online platform, through the TABNET app. Data were filtered using the dependent variable "Robson's groups" and the independent variable "type of delivery". The analysis was performed using Excel 2019 software through relative frequency and absolute frequency analysis. QGIS 3.34.0 was also used to construct a map by mesoregion of the State of Pará. In addition, the BioEstat 5.0 program was used to perform the ANOVA test and the graphic construction of a Box Plot. Conclusions: It is concluded that the majority of births in the State of Pará occurred by high delivery. The mesoregion with the highest rate of cesarean section and the highest number of cesarean sections per 1000 live births was Metropolitana de Belém, corresponding to 39.9% and 30.4%, respectively. The mesoregion with the lowest rate of cesarean deliveries and the lowest number of deliveries via discharge per 1000 live births was Marajó, equivalent to, respectively, 3.6% and 12.9. There was no significant variance in the mean number of cesarean sections between the mesoregions from 2019 to 2021 (F: 0.0585; p= 0.9432). The largest obstetric populations in the State of Pará were concentrated in groups 5, 1 and 3 of the Robson classification, considering that groups 5 and 1 had a greater predominance in all mesoregions of the State of Pará, corresponding to 31% and 19.2% of all cesarean sections in this State, respectively. This predominance was also maintained in the municipalities that had the highest rates of cesarean sections in each mesoregion. The high number of cesarean deliveries classified in group 11 compromises the real analysis of the distribution of deliveries via discharge in the other Robson groups.